Mobile Food Consumption Monitoring Application - Hamzeheinejad, Negin; Affal, Hannyzzura Pal @ (Journal of Food Technology Research, 2016)
Obesity is becoming a serious health issue due to the growing number of obese people in many countries. iFood, a mobile application to help individuals manage daily calorie consumption is presented and ways of optimizing the daily calorie needed is achieved by offering information of each food and suggestions on food and physical activities that can be carried out to balance the amount of calorie intake. The application is developed based on the Rational Unified Process Model (RUP) system development methodology which comprises of four stages including inception, elaboration, construction and transition. We present the design, implementation and evaluation of iFood for Android smartphones and demonstrate its feasibility in monitoring daily calorie intake. The application analyzes emphasizing on its accessibility and acceptance test. The results show that participants are satisfied with the features provided by the application. They agreed that the application helps them to monitor their food intakes and hence to lose weight.